Differentiation of Mouse Bone-Marrow Mesenchymal Stem Cells into Motor Neuron Cells in vitro. - Abdullah, Rafal Hussamildeen; Salih, Shahlla Mahdi; Yaseen, Nahi Yosef; Al-Shammari, Ahmed Majeed (Al-Nahrain Journal of Science, 2018)
Motor neuron cell is responsible for transfer neural instruct from brain to peripheral muscle through spinal cord; therefore any defect in these cells or spinal cord will affect motion. This study was designed to induce differentiation of Bone marrow mesenchymal stem cells (BM-MSCs) into neuron cells. BM-MSCs were isolated from bone stroma of femur and tibia of albino male mice and tested immunocytochemically for CD44, CD90, and CD105 expression and showed positive staining, while showed negative staining for CD34. Differentiation of BM-MSCs to motor neuron involved two main steps. Firs; induction of BM-MSCs by addition of 1mM mercaptoethanol (BME) in fetal bovine serum (FBS) in minimum essential medium MEM for 24 h and 2mM BME in free serum media for 2h. In the second step of induction retinoic acid, sonic hedgehog and nerve growth factor were added in free serum MEM for 4 days. Results revealed that the differentiation medium used was very efficient in directing the BM-MSCs to motor neural cell and showed positive reactivity to specific motor neural markers that used for detection of motor neuron cells like microtubule associated protein-2 antibodies and acetylcholine transferase antibody.